Hormonal Changes in a Sample of Iraqi Women and their Relationship to Liver Dysfunction - Nsaief, Reham Kassim; Ibraheem, Shaima R. (Iraqi Journal of Science, 2024)
There are numerous bidirectional interactions between the reproductive system and the liver. Sex steroids regulate metabolic health through signaling effects in both peripheral and central metabolic tissues, including adipose tissue, liver, skeletal muscle, and brain, and have a role in the etiology of structural and functional liver diseases. Blood samples were obtained from 90 healthy women (control group) and 90 women that have hormonal changes (patients’ group). The levels of reproductive hormones (follicle stimulation hormone/FSH, luteinizing hormone/LH, estradiol/E2, progesterone/P4) were measured by using fully automated Cobas E411, whereas those of liver enzymes (alanine transaminase /ALT, aspartate aminotransferase/AST, alkaline phosphatase/ALP) were measured by using fully automated Cobas C111. Levels of copper and ceruloplasmin were measured as well. The results demonstrate a strongly significant positive correlation between the levels of FSH and ALT (r = 0.45, p = 0.0001), FSH and AST (r = 0.48, p = 0.0001), and FSH and ALP (r = 0.303, p = 0.005), LH and ALT (r = 0.301, p = 0.005), LH and AST (r = 0.34, p = 0.001), and LH and ALP (r = 0.307, p = 0.004). The reproductive hormones and liver enzymes had a strong positive correlation. The results demonstrate a correlation between estrogen and copper (r = 0.38, p = 0.0001), as well as a highly significant positive correlation between estrogen and ceruloplasmin (r = 0.43, p = 0.0001) and a positive significant correlation between progesterone and copper (r = 0.26, p = 0.01). These findings are consistent with earlier research that has found a clear link between low estrogen levels in the blood and liver disease in women. These findings imply that an abnormally low level of estrogen may render women more susceptible to developing liver damage.